The Effect of Financial Attitude, Financial Literacy, and Financial Technology on Financial Inclusion With Financial Self-Efficacy as a Mediator: A Study on FEB Students at State Universities in Surabaya - Zulfialdi, M. Farid; Hartono, Ulil; Haryono, Nadia Asandimitra (Universitas Syiah Kuala, 2025)
This study aims to analyze the influence of financial attitude, financial literacy, and financial technology on financial inclusion with financial self-efficacy as a mediating variable among students of the Faculty of Economics and Business at public universities in Surabaya. This research uses a quantitative approach, with data collected through questionnaires distributed to 209 respondents selected using purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with AMOS software. The results show that financial attitude and financial literacy do not significantly affect financial self-efficacy, while financial technology has a significant effect. Furthermore, financial attitude and financial technology have a positive effect on financial inclusion, whereas financial literacy does not show a significant effect. The mediation test reveals that financial self-efficacy only mediates the relationship between financial literacy and financial inclusion. These findings emphasize the importance of strengthening self-efficacy and utilizing digital financial technology as effective strategies to encourage student participation in formal financial systems.